Microfilament Depolymerization Is a Pre-requisite for Stem Cell Formation During In vitro Shoot Regeneration in Arabidopsis - Tang, Li Ping; Li, Xiao Ming; Dong, Yu Xiu; Zhang, Xian Sheng; Su, Ying Hua (Frontiers in Plant Science, 2017)
De novo shoot regeneration is widely used in fundamental studies and agricultural applications. Actin microfilaments are involved in many aspects of plant cell division, cell morphogenesis and cell signal transduction. However, the function of actin microfilaments during de novo shoot regeneration is poorly understood. Here, we investigated the organization of actin microfilaments during this process and found that stem cell formation was associated with microfilament depolymerization. Furthermore, inhibition of microfilament depolymerization by phalloidin treatment or downregulation of actin depolymerizing factors (ADFs) restrained stem cell initiation and shoot regeneration. Inhibition of ADF expression affected the architecture of microfilaments during stem cell formation, and the polar transport and distribution of auxin were also disrupted. Together, our results demonstrate that organization of the microfilament cytoskeleton play important roles in stem cell formation and shoot meristem induction during shoot regeneration.